2017
DOI: 10.3389/fneur.2017.00004
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Hemorrhagic Edema and Secondary Hematoma Expansion after Intracerebral Hemorrhage: From Benchwork to Practical Aspects

Abstract: Spontaneous intracerebral hemorrhage (SICH) is the most lethal type of stroke. Half of these deaths occur within the acute phase. Frequently observed deterioration during the acute phase is often due to rebleeding or peri-hematomal expansion. The exact pathogenesis that leads to rebleeding or peri-hemorrhagic edema remains under much controversy. Numerous trials have investigated potential predictor of peri-hemorrhagic edema formation or rebleeding but have yet to come with consistent results. Unfortunately, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
1
5
0
2
Order By: Relevance
“…Many studies have demonstrated the association of UCH-L1 and GFAP levels in serum with moderate or severe TBI 34 , 36 . Levels of GFAP within the serum have been linked to ensuing gross brain pathology, such as lesions, contusions and hemorrhages 45 , however, as our cFPI model of mTBI in micro pigs does not produce such focal injuries 29 , the change in serum GFAP following cFPI cannot be associated with gross pathologies. Clinical studies have demonstrated that the levels of circulating GFAP within the first day post-injury could also be associated with the presence of more subtle pathologies, including DAI 21 – 23 .…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have demonstrated the association of UCH-L1 and GFAP levels in serum with moderate or severe TBI 34 , 36 . Levels of GFAP within the serum have been linked to ensuing gross brain pathology, such as lesions, contusions and hemorrhages 45 , however, as our cFPI model of mTBI in micro pigs does not produce such focal injuries 29 , the change in serum GFAP following cFPI cannot be associated with gross pathologies. Clinical studies have demonstrated that the levels of circulating GFAP within the first day post-injury could also be associated with the presence of more subtle pathologies, including DAI 21 – 23 .…”
Section: Discussionmentioning
confidence: 91%
“…There are many in vitro reports that showed good neuroprotective properties of amifostine against cisplatin and oxaliplatin, and some studies on patients claiming promising effects of amifostine against peripheral neurotoxicity induced by cisplatin, oxaliplatin, and carboplatin [ 99 , 100 ]. Moreover, a network meta-analysis of Fu and coworkers [ 76 ] confirmed that amifostine was the most active against both overall and severe platinum drugs-induced neurotoxicities compared to other most used therapies, such as vitamin E, GSH, and Ca/Mg infusion. Metformin, an anti-diabetic drug, showed neuroprotective effects against other chemotherapy-induced neuropathies, and therefore it has recently been tested in vivo for alleviating the oxaliplatin-induced neuropathy in rats.…”
Section: Antioxidants In the Treatment Of Platinum-based Chemothermentioning
confidence: 99%
“…In fact, it is not clear if the tissue of restricted diffusion (L ADC ) is assigned to disappear or may be part of a potential therapeutic target. 40 Recent studies showed that perihematomal diffusion restriction depends on ICH volume, but does not independently predict outcome although the diffusion restriction correlated with in-hospital mortality and disability rate or death. 41 However, other studies indicate that the perihematomal edema expansion is associated with poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 97%